Mouse Vα14i natural killer T cells are resistant to cytokine polarization in vivo - Matsuda, Jennifer L. (National Academy of Sciences, 2003)
Under different circumstances, natural killer T (NKT) cells can cause a T helper (Th) 1 or a Th2 polarization of immune responses. We show here, however, that mouse NKT cells with an invariant Vα14 rearrangement (Vα14i NKT cells) rapidly produce both IL-4 and IFN-γ, and this pattern could not be altered by methods that polarize naive CD4(+) T cells. Surprisingly, although cytokine protein was detected only after activation, resting Vα14i NKT cells contained IL-4 and IFN-γ mRNAs. Despite this finding, in vivo priming of mice with the glycolipid antigen recognized by Vα14i NKT cells resulted in a more Th2-oriented response upon antigen re-exposure. The Vα14i NKT cells from primed mice retain the ability to produce IL-4 and IFN-γ, but they are less effective at activating NK cells to produce IFN-γ. Our data therefore indicate that Vα14i NKT cells have a relatively inflexible immediate cytokine response, but that changes in their ability to induce IFN-γ secretion by NK cells may determine the extent to which they promote Th1 responses.